II. Mahmud askeri yapılarından Davudpaşa Kışlası - Dalğın, Yonca (My University, 2019)
Bu tez, stratejik bir öneme haiz ve modern kışlalara örnek gösterilebilecek olan Davudpaşa Kışlası’nı belgeler ışığında incelemeyi amaçlamıştır. Bina tarihi çalışması olarak ele alınması gereken tezde, bugüne kadar yapılmış araştırmalardan farklı olarak, II. Mahmud döneminde yaşanan iç ve dış gailelerin de bazalınması ve arşiv kaynaklarının olabildiğince kullanılmasıdır. Araştırma eserlerde elde edilen bilgilerin çoğu, arşiv araştırmalarının eksik yapılması, belgelerin sadece özetlerinin okunması veya yanlış okunmasından dolayı yanlış sonuçlar elde edilmesine sebebiyet vermiştir. Aynı zamanda binaya ait keşif ve tamir defterlerinin incelenmemiş olduğu da varsayılırsa eksik ve yanlış olan kısımlar belgeler ışığında tamamlanmıştır. Osmanlı Devleti, II. Mahmud, Asâkir-i Mansûre-i Muhammediye, Davudpaşa Kışlası.

This thesis purposes to focus on Davudpasa Barracks, which is vested with strategic importance and isan example of modern barracks. The thesis that should be considered as the study of building history, unlike the researches conducted up to the present, predicated on the internal and external struggles of the period of Mahmud the second and benefited from archieve resources as much as possible. Inthemost of thedata obtained in the research, incorrectin ferences have been obtain eddueto the lack of archivalresearch, onlyreading of the abstract sor misreading of the documents. Besides, assumming that the examination sandex plorations of there pair documents of buildingarein complete, missing and incorrect partsare completed with in the thesis in the light of documents. Ottoman State, Mahmud the second, Asâkir-i Mansûre-i Muhammediye, Davudpaşa Barracks
Keywords: Davudpaşa Kışlası Davudpaşa Barracks; History; Tarih; Turkey; Türkiye